Words to live by : journeys in ancient and modern Egyptian monasticism - Vivian, Tim.; Athanassakis, Apostolos N.; Mikhail, Maged S. A., 1974-; Pearson, Birger A. (Birger Albert), 1934- (Kalamazoo, Mich. : Cistercian Publications, 2005)
"Personal accounts of journeys to present-day monasteries in Egypt and translations of ancient monastic texts"--Provided by publisher.
Words to live by -- The monasteries of the Wadi al-Natrun, Egypt : a monastic and personal journey -- A journey to the interior : the monasteries of Saint Antony and Saint Paul by the Red Sea -- The good God, the Holy Power, and the Paraclete : ad filios Dei (to the sons of God) by Saint Macarius the Great -- Saint Paul of Tamma and the life of the cell -- The life of Paul of Tamma -- Four short works -- On the cell -- Monks, middle Egypt, and Metanoia : the life of Apa Phib -- Humility and resistance in late antique Egypt : the life of Longinus -- The ascetic discourse of Stephen of Thebes -- Holy men and businessmen : monks as intercessors in fourth-century Egypt.
Map on p. [2] and [3] of cover.
Includes bibliographical references (p. 395-416) and index.
Keywords: Vivian, Tim -- Travel; Monastic and religious life -- History -- Early church, ca. 30-600 -- Sources; Monastic and religious life -- Egypt -- History -- Sources; Monastic and religious life -- Egypt; Egypt -- Description and travel